2013
DOI: 10.1038/srep01678
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-II forms potential “landing terrain” for lantibiotics in simulated bacterial membrane

Abstract: Bacterial cell wall is targeted by many antibiotics. Among them are lantibiotics, which realize their function via interaction with plasma membrane lipid-II molecule — a chemically conserved part of the cell wall synthesis pathway. To investigate structural and dynamic properties of this molecule, we have performed a series of nearly microsecond-long molecular dynamics simulations of lipid-II and some of its analogs in zwitterionic single component and charged mixed simulated phospholipid bilayers (the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 44 publications
8
78
0
3
Order By: Relevance
“…Then, the observed behavior of the C―H stretching bands suggests that the LII is able to penetrate deep inside the bilayer in the L α state. A recent study of the conformational properties of LII in bacterial membranes by molecular dynamic (MD) simulations has shown that the long bactoprenol tail of LII can penetrate the hydrophobic membrane region and adopts different conformations, being the most typical that with the terminal part of the tail residing between two monolayers . This simulated behavior of LII in a fluid lipid membrane supports our spectral observations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Then, the observed behavior of the C―H stretching bands suggests that the LII is able to penetrate deep inside the bilayer in the L α state. A recent study of the conformational properties of LII in bacterial membranes by molecular dynamic (MD) simulations has shown that the long bactoprenol tail of LII can penetrate the hydrophobic membrane region and adopts different conformations, being the most typical that with the terminal part of the tail residing between two monolayers . This simulated behavior of LII in a fluid lipid membrane supports our spectral observations.…”
Section: Resultssupporting
confidence: 87%
“…This interaction has been extensively studied with the aim of reaching an understanding at the molecular level of bactericidal activity of nisin, suitable to be applied to the development of new antibiotics . On the other hand, a recent computational study of LII in anionic simulated membranes revealed the formation of an ‘amphiphilic pattern’ around the LII headgroup on the bilayer surface because of the insertion of the bactoprenol tail into the hydrophobic membrane region, and suggested the importance of this pattern in the recognition process of LII receptor by antibiotics . To obtain a complete picture of these phenomena, it is essential to rely on experimental tools to provide additional structural and mechanistic information.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we use a penta-peptide of the amino acids L-Ala-γ-D-Glu-LLys-D-Ala-D-Ala that has been used in several other studies. 5,7,[29][30][31][32] The peptidoglycan of S. aureus also contain a pentaglycin interpeptide bridge 33 attached to the Lys residue, but this was omitted both for simplicity and to be consistent with other studies. 5,7,[30][31][32] Full details of the model are provided in the SI.…”
Section: Lipid IImentioning
confidence: 99%
“…Da die Geschwindigkeit der bakteriellen Zellwandbiosynthese offenbar auch über die durchgehend niedrige Konzentration an Lipid II geregelt wird, wurde Lipid II schon mehrfach in der Evolution als wertvolles antibakterielles Target genutzt. [5] Zahlreiche hochpotente Antibiotika interagieren mit Lipid II, das eine regelrechte "Landungsplattform" [6] für depsipeptidartige Strukturen, wie z. B. Katanosin B( Lysobactin), Plusbacin, Enduracidin und Ramoplanin zu sein scheint.…”
Section: Methodsunclassified